Obesidade abdominal dinapênica e suas repercussões sobre o metabolismo dos carboidratos, lipídeos, incidência de síndrome metabólica e mortalidade por doenças cardiovasculares em pessoas maiores de 50 anos - Ramírez Muñoz, Paula Camila (2022)
Among physical and metabolic changes in the aging process, obesity and dynapenia stand out. Although some cross-sectional evidence demonstrates that dynapenic abdominal obesity (AO/D) defined as a combination of decreased neuromuscular strength and central obesity, may further impair carbohydrate and lipid metabolism as well as increase the risk of metabolic syndrome and mortality from cardiovascular diseases than dynapenia or obesity alone. To the best of our knowledge, no longitudinal studies have evaluated such hypotheses. Thus, the present thesis has three objectives: 1) To analyze whether AO/D impairs the trajectories of the lipid profile and carbohydrate metabolism and whether there are gender differences in these trajectories, 2) To analyze whether AO/D is a risk factor for the incidence of metabolic syndrome, and 3) To analyze whether AO/D increases the risk of cardiovascular mortality. In order to respond the proposed objectives, individuals aged 50 years or older participating in the English Longitudinal Study of Ageing (ELSA) were analyzed. Dynapenic abdominal obesity was defined based on waist circumference (> 102 cm for men and > 88 cm for women) and grip strength (< 26 kg for men and < 16 kg for women). The participants were classified as non-abdominally obese/non-dynapenic (NAO/ND), abdominally obese/non-dynapenic (AO/ND), non-abdominally obese/dynapenic (NAO/D) and abdominally obese/dynapenic (AO/D). To study the trajectory of carbohydrate and lipid metabolism, the dependent variables were the levels of glycated hemoglobin, fasting glucose, total cholesterol, LDL, HDL and triglycerides. The incidence of metabolic syndrome was analyzed as a dependent variable in objective two and mortality from cardiovascular diseases was the dependent variable in third objective. The follow-up time of the three studies was 8 years. The main results found were that men AO/D showed a trajectory of increase in serum levels of LDL cholesterol and a decline in glycemia and in glycated hemoglobin percentage (HbA1c) when compared to NAO/ND. Such differences were not observed in women. Furthermore, in both sexes, both AO/D and AO/ND were risk factors for the incidence of metabolic syndrome, however the effect size was greater in. AO/D. Finally, only AO/D was a risk factor for cardiovascular mortality for men and women. The evidence of this thesis indicates a synergistic action between abdominal obesity and dynapenia capable of altering LDL cholesterol, HbA1c and glucose metabolism in men as well as increasing the risk of metabolic syndrome and cardiovascular mortality in both sexes. Such findings have clinical relevance since both conditions can be prevented to mitigate their harmful effects in people over 50 years of age.